PENGARUH KOMBINASI DOSIS PUPUK ORGANIK DAN ANORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH - Fauzia Hulopi (Universitas Tribhuwana Tunggadewi, 2008)
This research aimed to study the influence of inorganic and organic manure combination rate on peanut crop yield and growth. The experiment applied randomized block design which was arranged as factorial. The first factor was rate of farmyard manure and the second factor was rate NPK fertilizer. Data were collected through measurements of plant high, number of branch, number of leaves, plant biomass weight, heavy and wet heavy run dry polong, number of polong and heavy 100 dry seed. The results showed that there are real interaction between treatment of organic manure and inorganic manure to component of vegetative and generative except plant biomass weight. combination farmyard manure 1 kg /plot and NPK fertilize 20 g /plot (A1N1) represent optimum dose at peanut crop conducting posed at by variable is number of polong equal to 21.07 polong, weight of polong equal to 63.16 g, dry weight of polong equal to 37.74 g and 100 dry seed equal to 47.79 g/ plant